Nonparametric bounds on employment and income effects of continuous vocational training in East Germany - Michael Lechner (Zentrum für Europäische Wirtschaftsforschung (ZEW); ZBW – Leibniz Information Centre for Economics, 1996)
This paper explores the potential of an approach suggested by Manski of obtaining nonparametric bounds for treatment effects in evaluation studies without knowledge of the participation process. The practical concern is the effects of continuous vocational training in East Germany. The empirical application is based on a large cross-section that covers about 0.6% of the total population in 1993. The results are rather mixed. The large width of the intervals obtained emphasise the fundamental problem of all evaluation studies without good knowledge of the relationship between potential outcomes and the participation process. However, in some cases suitable exclusion restrictions are indeed capable of bounding the treatment effects strictly away from zero.
Keywords: C14; C49; J24; J31; 330; Nonparametric estimation of treatment effects; training evaluation; East German labour markets; Mikrozensus; Berufsbildung; Wirtschaftspolitische Wirkungsanalyse; Schätztheorie; Bildungsertrag; Arbeitsmarkt; Neue Bundesländer